2011
DOI: 10.1080/02687038.2011.577284
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of language processing in aphasia: Improving activation and maintenance of linguistic representations in (verbal) short-term memory

Abstract: Background Verbal short-term memory (STM) impairments are invariably present in aphasia. Word processing involves a minimal form of verbal STM, i.e., the time course over which semantic and phonological representations are activated and maintained until they are comprehended, produced, or repeated. Thus it is reasonable that impairments of word processing and verbal STM may co-occur. The co-occurrence of language and STM impairments in aphasia has motivated an active area of research that has revealed much abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 64 publications
0
37
1
Order By: Relevance
“…They were also tested with selected language and verbal span measures to ascertain the normality of their language-processing abilities. The tests included the standardised Finnish version of the Boston Naming Test (BNT; Laine, Koivuselkä-Sallinen, Hänninen, & Niemi, 1997), phonological and semantic fluency tasks, narration, the semantic odd-one-out 1 The Temple Assessment of Language and Short-term Memory in Aphasia (TALSA) is a comprehensive test battery designed for evaluating language and verbal short-term memory abilities in aphasia (Martin et al, 2010;Kalinyak-Fliszar et al, 2011). In TALSA, short-term memory load (as number of alternatives to be compared or as different intervals between stimulus and response) are varied systematically across language tasks.…”
Section: Methodsmentioning
confidence: 99%
“…They were also tested with selected language and verbal span measures to ascertain the normality of their language-processing abilities. The tests included the standardised Finnish version of the Boston Naming Test (BNT; Laine, Koivuselkä-Sallinen, Hänninen, & Niemi, 1997), phonological and semantic fluency tasks, narration, the semantic odd-one-out 1 The Temple Assessment of Language and Short-term Memory in Aphasia (TALSA) is a comprehensive test battery designed for evaluating language and verbal short-term memory abilities in aphasia (Martin et al, 2010;Kalinyak-Fliszar et al, 2011). In TALSA, short-term memory load (as number of alternatives to be compared or as different intervals between stimulus and response) are varied systematically across language tasks.…”
Section: Methodsmentioning
confidence: 99%
“…The speakers reported in other STM studies (Koenig-Bruhin & Studer-Eichenberger, 2007;Majerus et al, 2005;Murray et al, 2006) showed smaller improvements in digit repetition after treatment. The speaker reported by Kalinyak-Fliszar et al (2011) did not improve in this task. Although the listening span does not require speech output but forward digit span does, they both involve either recognition or recall of the serial order of words, both of which are measures of STM (Jefferies et al, 2006).…”
Section: Discussionmentioning
confidence: 54%
“…Currently, different authors have developed different verbal WM assessment instruments, inspired by different theoretical models (e.g., Harris et al, 2014;Kalinyak-Fliszar et al, 2011;Majerus et al, 2015;Vallat et al, 2014). A comprehensive WM test battery that would target the different WM components discussed here in a process-specific and integrated manner is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive WM test battery that would target the different WM components discussed here in a process-specific and integrated manner is still lacking. Although there have been some standardization efforts for a subset of the tasks and instruments presented here (e.g., Kalinyak-Fliszar et al, 2011;Majerus et al, 2015), standardized, psychometrically valid and theoretically-informed WM test batteries, particularly for use in severely impaired patients such as aphasic patients, remain scarce (Murray, Salis, Martin, & Dralle, 2016). By explicitly characterizing the storage versus processing requirements as well as the attentional and executive processes involved in all types of WM tasks, a theoretically-informed WM battery could also be a step toward the resolution of the debate around the distinction of 'working memory' versus 'short-term memory' tasks.…”
Section: Discussionmentioning
confidence: 99%